The relationship between consumer behavior and food labelling effectiveness: moderating effect of consumer motivation / Maznah Wan Omar … [et al.] - Wan Omar, Maznah; Zakaria, Azfahanee; Mohd Ali, Mohd Noor; Syed Ahmad Alhady, Syed Mohammed Alhady (2011)
Majority of consumers consider food labelling to be very important component of their lifestyle and regard nutrition as a positive attribute to the food products. Therefore, food labelling has to be informative and attractive in order to grab’s consumer’s attention. As such, labels are part of the information set used by consumers in making product-purchasing decisions.